Analisis Biomekanika Transfer Gaya Kinetic Chain Upper–Lower Limb pada Medicine Chest Pass dan Standing Broad Jump Atlet (SPOBNAS) NTT - Salmon Runesi; Andreas Johanis Fredik Lumba; Christin Prima Mery Rajagukguk; Dilli Dwi Kuswoyo (Universitas Hamzanwadi, 2026)
Energy transfer through the kinetic chain is a fundamental concept in explosive athletic movements. However, studies comparing the force transfer mechanisms between upper-limb and lower-limb movements, particularly in athletes in Eastern Indonesia, are still limited. This study aims to analyze and compare the biomechanical mechanisms of force transfer in the upper-lower limb kinetic chain through the Medicine Chest Pass (MCP) and Standing Broad Jump (SBJ) in SPOBNAS athletes in NTT Province. The study used a quantitative approach with a comparative and correlational design. A total of 18 athletes were divided into two groups: the MCP group (n=9) and the SBJ group (n=9). Data were collected through MCP and SBJ tests with three trials, and the best scores were recorded. Data analysis included descriptive statistics, Shapiro-Wilk normality test, Levene's homogeneity test, independent t-test, and Pearson correlation test. The results showed a significant difference between MCP and SBJ scores (p < 0.05; Cohen's d = 0.95), indicating a difference in force transfer characteristics between the two movements. Correlation analysis showed a moderate and significant positive relationship between SBJ and MCP (r = 0.47; p < 0.05; r² = 0.22). It can be concluded that MCP and SBJ represent different but interrelated kinetic chain patterns.